ANALISIS UNSUR INTRINSIK CERITA RAKYAT OIL LELANG (SULTAN NAJJAMUDIN) DARI DESA HULNANI - Luthfiyah R.A Tonu; Marselus Robot; Karolus B. Jama (Journal Education and Government Wiyata, 2025)
This study aims to identify and describe the intrinsic elements of the folklore "Oil Lelang (Sultan Najjamudin)" originating from Hulnani Village, Alor Barat Laut Regency, East Nusa Tenggara. The research applies a structural approach with a descriptive qualitative method. The data were obtained from oral narratives passed down through generations and documented by the local Afen Lelang tribe. The focus of analysis includes theme, plot, characters and characterization, setting, point of view, language style, and moral message. The results reveal that the story embodies themes of perseverance and Islamic proselytization, with a linear plot and religious characters who demonstrate strong personal values. The moral messages conveyed reflect Islamic values and local wisdom. This folklore serves as an educational medium for character development and the preservation of local culture.